The Perception of Economic and Financial Condition of Enterprises After the First Period of Covid-19 Pandemic in The Opinion of Managers of Podkarpackie Voivodship in Poland in The Light of Results of Other Surveys - Piotr WALENTYNOWICZ; Renata SZANTER (Communications of International Proceedings, 2021)
The Covid-19 pandemic has changed the course of many businesses around the world. It pushed many companies into unfamiliar territory, some of them had to disappear from the market, others gained wind in their sails and sailed out into wider waters. The aim of this paper is to present the results of a study on the economic and financial condition of enterprises in the Podkarpackie voivodship after the first period of the pandemic caused by the SARS-CoV-2 virus, as a case study of how companies in Poland dealt with these difficult conditions. It also presented the point of view of the representatives of these companies on the direction of changes that will occur in the environment under the influence of the pandemic in the future and related changes in their activities, to bring the atmosphere that accompanied the functioning of enterprises in Poland in the second half of 2020 (ie, after the first period of the pandemic). The results of this research are interesting because they were conducted using the primary research method (CATI), on a representative sample of 673 representatives of the surveyed companies in the Podkarpackie region. However, in order to draw conclusions to the extent to which they can be a reliable example for companies from all over Poland, in the further part of the article the results of this research were confronted with the effects of other studies based on literature studies and information from secondary sources. Consequently, in the final part of the paper conclusions are drawn on the situation in which enterprises in Poland, found themselves in connection with the occurrence of Covid-19 pandemic conditions.
Keywords: Covid-19 pandemic; economic and financial health; enterprises; Poland